A CONTEMPORARY RECAPITULATION OF MAJOR FINDINGS ON VEHICLE ROUTING PROBLEMS : MODELS AND METHODOLOGIES - Jayarathna, D. G. N. D.; Lanel, G. H. J.; Juman, Z.A.M.S. (International Journal of Recent Technology and Engineering (IJRTE), 2019)
In introdusing and designing innovative solutions to the problems related to transportation and distribution systems is a contemporary area in logistics. The ultimate objective of this paper is to initiate a thought provoking discusion on Vehicle Routing Problems (VRP) along with its modifications or changes which incorporates recent model developments and improvements. Both in operational research and computer science, VRP is a combinatorial optimization issue researched at length. Capacitated Vehicle Routing Problem (CVRP), Vehicle Routing Problem with Time Windows (VRPTW), Vehicle Routing Problem with MultiDepot (MDVRP) and other variants are integral components of VRP. In recent times, the areas of VRP categorization has been further discussed, the common constraints have been summarized and model algorithms have been developed. In toto the future model implications of VRP are analyzed and further, it is predicted that the Intelligent Vehicle Routing Problem and Intelligent Heuristic Algorithm would be an important arena of future researches
Keywords: Capacitated Vehicle Routing Problem, Exact Methods, Meta – Heuristics, Multi-Depot Vehicle Routing Problem